Biological properties of soils of the "Nadedzhdinsky" and "Severo-Kamyshansky" oil fi elds located in the territory of the "Mekletsky" reserve - Buluktaev, Aleksey A. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология, 2023)
The most acute environmental problem in many regions of Russia and other countries is environmental pollution with oil and oil products. Soil pollution with oil products can occur in various emergencies in areas of oil production and processing, when oil pipelines break, which causes leakage and spills on the soil surface, as well as in places where oil products are distributed. The purpose of this study is to study the biological properties of soils in Kalmykia under conditions of oil and oil products pollution. The soils of the Nadezhdinskoye and Severo-Kamyshanskoye oilfi elds located on the territory of the Mekletinsky nature reserve were chosen as the objects of study. Laboratory and analytical studies, as well as sampling, were carried out using methods generally accepted in biology and soil science. The content of oil products in the soils of the oil fi eld is in a wide range: from 0.4 to 12.5%. A negative correlation was established between the content of oil products in the soil and the activity of catalase and phosphatase. Oil products have a negative impact on the growth and development of radishes. The exploitation of oil fi elds in specially protected natural areas leads to the fl ow of oil and oil products into the environment. In the soils of Kalmykia on the territory of oil fi elds, under the infl uence of pollution with oil and oil products, the activity of soil enzymes is inhibited, in addition, the soils exhibit a high degree of phytotoxicity with respect to test plants.